The Radiant - The Otolith Group (United Kingdom, 2012)
The Radiant explores the aftermath of March 11 2011, when the Great Tohoku Earthquake struck the North East Coast of Japan at 2.46pm, triggering a tsunami that killed tens of thousands and causing the partial meltdown of the Fukushima Daiichi nuclear power plant. In the fissures opened by these catastrophes, The Radiant travels through time and space, invoking the historical promise of nuclear energy and summoning the future threat of radiation that converge upon the benighted present. Under these conditions, the illuminated cities and evacuated villages of Japan can be understood as a laboratory for the global nuclear regime that exposes its citizens to the necropolitics of radiation
Duration: 01:05:00
Keywords: Documentary films